PENGARUH MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK IPHONE DI KOTA MEDAN - Utami, Vivi Ayudhia; Amelia, Silvia; Suhairi, Suhairi (Universitas Labuhanbatu, 2021)
This study aims to determine the effect of brands and products on consumer purchasing decisions for cellphones. In this study, the type of research used is explanatory research or explanation, namely research that is used to explain the influence between variables through hypothesis testing that has been formulated. In this study, the research population was PS Store consumers who purchased iPhone products, which opened 58 respondents. Data collection techniques used are observation, interviews, and questionnaires. The data analysis technique used is a qualitative method with the calculation of the t test and f test. The results in this study are based on the results of calculations, it can be seen that the test results show that the entire arithmetic value of each variable is > ttable (2.0032). The biggest influence on the t test is the influence of brand image on purchasing decisions. The results of the F test show that there is an influence between brand image and product quality on purchasing decisions with the calculated F value (18.866) > F table (4.0130).